2011
DOI: 10.1111/j.1744-6570.2010.01203.x
|View full text |Cite
|
Sign up to set email alerts
|

Work Engagement: A Quantitative Review and Test of Its Relations With Task and Contextual Performance

Abstract: Many researchers have concerns about work engagement's distinction from other constructs and its theoretical merit. The goals of this study were to identify an agreed‐upon definition of engagement, to investigate its uniqueness, and to clarify its nomological network of constructs. Using a conceptual framework based on Macey and Schneider (2008; Industrial and Organizational Psychology, 1, 3–30), we found that engagement exhibits discriminant validity from, and criterion related validity over, job attitudes. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

114
2,220
12
88

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 2,146 publications
(2,617 citation statements)
references
References 184 publications
114
2,220
12
88
Order By: Relevance
“…This outcome was partially at variance with Macey and Schneider's (2008) framework which points to significant associations between engagement and employee discretionary work. Christian et al (2011) concluded, workers who had some measure of support, voice in decisions, and collegiality were more likely to be engaged, effective, and efficient workers in both mandatory and discretionary roles. This in turn, may lead to a more successful organization.…”
Section: Employee Engagement Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…This outcome was partially at variance with Macey and Schneider's (2008) framework which points to significant associations between engagement and employee discretionary work. Christian et al (2011) concluded, workers who had some measure of support, voice in decisions, and collegiality were more likely to be engaged, effective, and efficient workers in both mandatory and discretionary roles. This in turn, may lead to a more successful organization.…”
Section: Employee Engagement Frameworkmentioning
confidence: 99%
“…Macey and Schneider (2008) emphasized that engagement is not to be confused with job satisfaction; engagement is denoted by activation and energy (Christian et al, 2011). Whereas, job satisfaction is denoted by contentment or satiation rather than energy.…”
Section: Employee Engagement Frameworkmentioning
confidence: 99%
See 3 more Smart Citations